A necessidade torna o raciocínio elástico: análise dos textos dramáticos Um elefante no caos e Flávia, cabeça, tronco e membros, de Millôr Fernandes - Alice Carvalho Diniz Leite (2018)
This dissertation focuses on the analysis of two plays: Um elefante no caos ("An Elephant in Chaos") and Flávia, cabeça, tronco e membros ("Flavia, Head, Trunk and Members"), both written by the playwright Millôr Fernandes, in 1955 and 1963, respectively. The methodology used in this study includes three different theoretical paths that converge in the end. The initial objective of this work is to identify the elements that constitute a fable characters, time, space and dramatic genre and the vectors that propel the action in each of the theatrical texts. To fulfill this objective it is fundamental to use the works of Patrice Pavis, Agapito Martinez, Tadeusz Kowzan and Jean-Pierre Ryngaert as guides. In a parallel and complementary way, it is possible to observe a constant habit of the dramatic figures within their dialogues in the two aforementioned texts: the act of balancing their private interests and the enforced laws through discourse. Therefore, the title of this dissertation, A necessidade torna o raciocínio elástico ("Reasoning Becomes Elastic Through Necessity"), is better understood when analyzed by such an angle. Flexible arguments, that shrink and extend according to necessity, are examined through the use of the new rhetoric of Chaïm Perelman and of the sophistic of Barbara Cassin. Finally, this dissertation also offers a recollection ofcases of Millôr Fernandes' life and works, as well as some academic considerations on the vast and varied work of the "carioca" (born in the city of Rio de Janeiro) author. Special emphasis is given to the contributions by Décio de Almeida Prado, Sábato Magaldi and JoãoRoberto Faria, for they offer important information regarding the creative nucleus of both plays selected to be part of this study. The works by Millôr Fernandes are versatile, and reveal great malleability in their forms and structures, attributing value to freedom in creation and refusing the framing of stagnated labels.